A Comparative Study of Nursing Educational System in Indonesia and Japan - Susiana Nugraha; Mika Tanaka; Ferry Efendi (Universitas Airlangga, 2008)
Introduction: According to Economic Partnership Agreement (EPA) between Indonesia and Japanese governments, Japanese government plans to recruit Indonesian nurses and caregivers to fulfill the demand of those positions at the hospital and health centers. However, to be a qualified worker in Japan, one has to pass a national examination that is conducted by the Minister of Health, Labor and Welfare for a license of a registered nurse within 3 or 4 years of working as a nurse or caregivers, respectively. Method: Having considered that matter, a comparative study of the background of educational systems in Indonesia and Japan is discussed in this paper, with particular reference to the Diploma 3 nursing program. Result: There is no specific difference between Indonesian and Japanese nursing educational systems. Discussion: However, current health condition of the countries remains as the focus of the curriculums where Indonesian nursing education is focusing on communicable disease and surgery nursing, whereas Japanese is focusing on gerontology and chronic disease nursing. In case of qualification method, Japanese nurses should undertake national board examination to be a qualified nurse. On the other hand, there is no national board examination for Indonesian nurses.